Global research trends in AI-related foot and ankle surgery research: A bibliometric and visualized study - Liyi Zhang; Hui Du (Journal of Orthopaedic Surgery)
Background Artificial intelligence (AI) has experienced rapid advancements leading to numerous applications in foot and ankle surgery. This study aimed to assess the current status, research trends, and future directions of AI in foot and ankle surgery and to identify emerging hotspots in this field. Methods Relevant publications on AI in foot and ankle surgery were retrieved from the Web of Science Core Collection database up to December 31, 2024. A bibliometric analysis was conducted, and data visualization was performed using VOSviewer and CiteSpace. Results A total of 2047 publications from 1999 to 2024 were included. The number of AI-related studies in foot and ankle surgery has shown a steady annual increase. China (581 publications, H-index = 47) and the United States (489 publications, H-index = 53) are the leading contributors in terms of publication volume and research impact. Keyword co-occurrence analysis indicates that AI research in this field has progressed from foundational algorithms to the study of lower limb kinematics and clinical disease applications. Keyword burst analysis highlights diabetic foot ulcers and computer-aided diagnosis as key research focuses and emerging hotspots for future investigation. Conclusion AI research in foot and ankle surgery has expanded rapidly, with China and the United States at the forefront. The field has evolved from algorithm development to applications in lower limb kinematics and clinical disease management, with diabetic foot ulcers and computer-aided diagnosis identified as major areas of future research.